Uncovering hidden enhancers through unbiased in vivo testing - Brandon J. Mannion; Stella Tran; Ingrid Plajzer-Frick; Catherine S. Novak; Veena Afzal; Jennifer A. Akiyama; Ismael Sospedra-Arrufat; Sarah Barton; Erik Beckman; Tyler H. Garvin; Patrick Godfrey; Janeth Godoy; et al. (Nature Communications)
Abstract Chromatin signatures are widely used to identify tissue-specific in vivo enhancers, but their sensitivity and specificity remains unclear. Here we show that many developmental enhancers remain undetectable using currently available chromatin data. In an initial comparison of over 1200 developmental enhancers with tissue-matched chromatin data, 14% (n = 285) lacked canonical enhancer-associated chromatin signatures. To further assess the prevalence of enhancers missed by chromatin profiling approaches, we used a high-throughput transgenic enhancer assay to screen the regulatory landscapes of two key developmental genes at 5 kb resolution, spanning 1.3 Mb of mouse sequence in total. We observed that 23 of 88 (26%) in vivo enhancers discovered by this approach lacked enhancer-associated chromatin signatures in the respective tissue. Our findings suggest the existence of tens of thousands of enhancers that remain undiscovered by currently available chromatin data, underscoring the continued need for expanding resources for enhancer discovery.